PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS APLIKASI ELEKTRONIK BUMDESA SUGIHWARAS (e-BES) DI DESA SUGIHWARAS KECAMATAN CANDI KABUPATEN SIDOARJO - Yasmin Afandi; Ananta Prathama (Jurnal Noken: Ilmu-Ilmu Sosial, 2022)
Community economic empowerment is very necessary, especially in rural areas. Economic empowerment to strengthen the community through efforts owned by the community to get adequate income, obtain information, gain knowledge and skills, so it is expected to have an impact on improving economic results. This study aims to describe the Economic Empowerment of the community based on electronic applications BUMDesa Sugihwaras (E-BES) in Sugihwaras Village Candi District Sidoarjo regency. The type of research used in this study is descriptive with a qualitative approach. The focus of this study uses the empowerment approach (5p) proposed by Suharto cited by Hamid (2018), namely the possibility, strengthening, protection, support, and maintenance. Then the data sources in this study are primary data sources and secondary data sources. Primary data obtained from informants who have been appointed, documentation and observations made. While the secondary data in this study is to complement the needs of research data. The results of this study indicate that the Economic Empowerment of the community based on the electronic application of Sugihwaras village (E-BES) in Sugihwaras Village, Candi District, Sidoarjo regency has not been implemented in its entirety. It can be seen that the possibility is only done well while the strengthening and maintenance has been carried out but not optimal and protection, support has not been implemented by BUMDesa Sukses with Sugihwaras Village, Candi District, Sidoarjo regency